A Field Study of the Role of Human Resources Training to Improve the Quality of the Algerian Hotel Services - Hachemi , Benouadah; Ammar , Benaichi (The Arab Journal of Administration, 2018)
The study aims to find out the role of human resources training to improve the quality of the Algerian hotel services, a field study for the following hotels: Alziban Hotel, Nasib Hotel, Bath Hotel Biskra righteous state, the Castle Hotel liquefied state. In order to achieve that, the researchers choose a stratified random sample of (hotel manager, head of department, head of the branch, Chairman of the Group) and the 70 president of the individuals working in hotels, the study concludes: The existence of a correlation between the training of human resources and improve the quality of the Algerian hotel services. There is a role for training human resources in improving the quality of the Algerian hotel services. The study also recommended that the continuity in the training of human resources, which clearly affects the Algerian improve the quality of hotel services The hotel activity of the most advanced economic activities in all parts of the world, success depends on the success of hotel facilities management and the extent of their understanding of the nature of EDM, as well as human resource efficiency. The training of human resources factor in achieving the quality of hotel services and achieve a competitive advantage in this sector, saw researchers in that it is necessary to take a look at the training process and its importance in raising the efficiency of human resources working in hotels and the impact in improving the level of hotel services. It is also the subject of the quality of hotel services of the topics that gained the attention of various researchers in the field of marketing and tourism, especially those who are seeking to satisfy the needs and the desires and needs of their clients. Service organizations have realized, including the hotels that provide high-quality service is the most effective methods to ensure superiority over its competitors service organization, service organization where you can guarantee for itself a distinct competitive position among the organizations competition by offering quality service in line with customer requirements.